Prioritizing value chains for climate-smart agriculture (CSA) promotion in Mali, Niger and Senegal - Ouédraogo, Mathieu; Jaquet, Stéphanie; Traoré, Bouba; Sall, Moussa; Tougiani, Abasse; Dembélé, Siaka; Zougmoré, Robert B. (2021)
Climate change is already having a significant effect on agriculture and food security in West Africa. Climate-smart agriculture (CSA) is proposed as a solution to transform and reorient agricultural systems to support food security under the new realities of climate change. To benefit from the positive gains arising from CSA, a wide scale adoption of CSA technologies and practices is required. The value chain (VC) approach is positioning as a major upscaling opportunity for agricultural innovations in general and CSA options in particular as it offers opportunities to address most of adoption constraints of CSA. Through ensuring an effective and efficient coordination among its actors and creating partnerships with other stakeholders (such as public-private, private-cooperatives and related organizations along the VC), the VC approach improves the access to input and product markets and support the development of business services, contributing to promote the uptake of CSA technologies and practices. The Output 2 of the CCAFS- EU-IFAD-funded project “Building Livelihoods and Resilience to Climate Change in East and West Africa: Agricultural Research for Development (AR4D) for large-scale implementation of Climate-Smart Agriculture”, aims at developing climatesmart value chains to increase livelihood resilience in West Africa (Mali, Niger and Senegal). To reach this goal, the preliminary activity of the project was to conduct a series of stakeholders’ workshops in order to select promising VCs for the promotion of CSA in Mali, Niger and Senegal.